2013
DOI: 10.1111/jan.12071
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial influencers and mediators of treatment adherence in haemodialysis patients

Abstract: Strategies aimed at the development of successful adherence interventions should focus on reducing perceived barriers and enhancing self-efficacy and knowledge. It can be suggested that efforts to improve the healthcare provider-patient relationship would enhance adherence. In depressive patients, strategies that promote self-efficacy and the support of family or healthcare providers could diminish the negative impact of depression on adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 40 publications
(119 reference statements)
0
36
0
1
Order By: Relevance
“…Barriers resulting from oversight also emerge (Oh et al., ). Some studies have detected an inverse relationship between diet nonadherence and the perception of the patient in regard to their behaviour.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Barriers resulting from oversight also emerge (Oh et al., ). Some studies have detected an inverse relationship between diet nonadherence and the perception of the patient in regard to their behaviour.…”
Section: Resultsmentioning
confidence: 99%
“…Amongst the facilitators that enhance adherence to dietary and fluid restrictions, the perception or concept of disease was identified, together with self‐efficacy and the perception of control, which motivate adherence to healthy lifestyle habits (Clark et al., ; Khalil et al., ; Li et al., ; Mellon et al., ; Oh et al., ; Russel et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(9) Taking into consideration that adherence is a dynamic phenomenon that needs to be influenced by several factors and may change quite frequently, it is imperative that the health team develops strategies to constantly promote adherence behavior. (10) In Switzerland, a prospective, randomized study was developed that proposed to separate patients into two groups: one group would be submitted to the integrated care approach (IC) and the other to the usual care (HC) approach. The study showed that, after six months of follow-up, 84% of the patients submitted to the IC group achieved satisfactory parathormone levels, compared to 55% of the patients in the habitual care group.…”
Section: Resultsmentioning
confidence: 99%
“…A study on prevalence of adherence in an Indian population was very low because of perceived susceptibility and severity of hypertension among their study population 13 . This could be attributed to low literacy levels to understand hypertension and its consequences if not controlled and also lack of continuous medical education to patients by health workers.…”
Section: Knowledge Of Hemodialysis Patients On Antihypertensive Medicmentioning
confidence: 99%